Equity-Based Executive Compensation, Audit Committee Characteristics and Firm Financial Performance - Anaman, P.D. (University of Ghana, 2022)
This study, guided by agency theory and resource-based theory, analyses the impact of audit committee characteristics on the relationship between equity-based executive compensation and the financial performance of listed non-financial firms in Sub-Saharan African countries. This analysis relies on the financial expertise, gender diversity, and independence of audit committees. Over the research period of 2010-2019, 620 firm-year data were used in a panel regression analysis. According to the results, compensation for executives based on shareholding has a significant and negative impact on the company's profitability. In addition, the qualities of the audit committee employed in this research show a positive correlation to firm financial performance. Another key finding is that the relationship between equity-based executive compensation and firm financial performance is moderated in a positive and statistically significant way by the financial expertise and gender diversity of audit committees. When it comes to the relationship between equity-based executive compensation and firm financial performance, the moderating effect of audit committee independence was negative and significant. This research adds to what is known theoretically and empirically about the relationship between equity-based executive compensation, firm financial performance, and audit committee characteristics.
MPhil. Accounting
Keywords: Equity-Based Executive Compensation; Audit Committee